Sensation of Pain Using Buffered Lidocaine for Infiltration Before Vulvar Biopsy: A Randomized Controlled Trial. Issue 3 (March 2020) - Villavicencio, Jennifer C.; Kulkarni, Amita; Luis, Christine; Mendez, Heidy; Raker, Christina; Cronin, Beth; Robison, Katina
Abstract : OBJECTIVE: To evaluate the effects of buffered lidocaine on pain scores during vulvar biopsy. METHODS: We conducted a double-blind, randomized controlled trial, using prefilled, sequentially numbered, randomized syringes to infiltrate either 3 mL of buffered or nonbuffered lidocaine before vulvar biopsy. The primary outcome was a pain score marked on a 100-mm visual analog scale during infiltration. Secondary outcomes included pain scores after the procedure and change from baseline to infiltration. Participants were recruited to detect a clinically meaningful 15-mm difference in pain scores between groups. Sample size was calculated based on the null hypothesis that the mean pain score would be the same in women treated with buffered lidocaine as in those treated with nonbuffered placebo based on prior studies. Categorical data were compared by Fisher exact test, and continuous data were compared between groups by t -test or Wilcoxon rank sum test. RESULTS: From July 2015 to April 2018, 129 participants were randomized to one of two groups: nonbuffered lidocaine or buffered lidocaine. One hundred twenty-five were analyzed (nonbuffered n=62, buffered n=63). Four patients were excluded. The majority of participants were non-Hispanic white women with a mean age of 59 years. There was no difference in the primary outcome of pain during infiltration with a mean pain score of 35.8 mm in the buffered lidocaine group compared with 42.2 in the nonbuffered lidocaine group (mean difference −6.4; 95% CI −18.4 to 5.6; P =.3 by Wilcoxon rank sum test). There was also no difference in secondary outcomes of pain over the entire procedure (mean difference −0.3, 95% CI −9.7 to 9.2; P =.7) or change in pain from baseline to infiltration (mean difference −6.9, 95% CI −18.4 to 4.7; P =.2). CONCLUSION: There was no difference in pain scores during vulvar biopsy infiltration between the buffered and nonbuffered lidocaine groups. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT02698527. Abstract : Buffered lidocaine does not provide superior anesthesia compared with nonbuffered lidocaine during infiltration before vulvar biopsy.